Entwicklung eines auf Referenz-Petri-Netzen basierenden hybriden Simulationstools zur wissensbasierten Reduzierung des Energie- und Wasserbedarfs bei der Weinerzeugung - Schütz, Martin; Schwinn, Mira; Hussein, Mohamed; Gatternig, Bernhard; Groß, Frauke; Durner, Dominik; Fischer, Ulrich; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
The objective of the research presented here was the development of a Reference-Petri Net-work-based hybrid simulation tool for the knowledge-based reduction of energy and water re-quirements in wine production. Data surveys on the water and electrical energy requirements, based on 1000 liters of the finished product, reveal deviations that in some cases significantly exceed the factor of 10. Using the developed simulation tool, winemaking processes in indi-vidual companies can be simulated and analysed for weak points. The hybrid tool uses Refer-ence-Petri-Nets as a structuring element. A developed basic structure enables the creation of a "virtual twin" of existing wine businesses as well as various calculations and output options for the individual processes by the user. Comparisons of different actions and expenditure of savings potential bring a new transparency into the overall process chain of winemakin
Keywords: Prozessvirtualisierung; Modellierung und Simulation; Energiemanagement; Referenznetze